Beyond 1776 : globalizing the cultures of the American Revolution - O'Malley, Maria, 1976-; Van Renen, Denys (University of Virginia Press, 2018)
"These essays consider the American Revolution in new contexts, elucidating global interdependencies that took root in the eighteenth century through unlikely alliances, cultural transmissions, and complex networks of trade. The first part of the book centers on migration of ideas across cultures on the Continent, Scotland, and Ireland, particularly among intellectuals and through print. The essays in the second section articulate how revolutions fostered largely unacknowledged transatlantic and transoceanic exchanges, in the West Indies and in the first penal colonies of Australia, along the Celtic Fringe and Pacific Rim, and in the vast territories through which slavery circulated. The contributors examine a range of texts, from novels and drama to diplomatic correspondence, letters of common sailors, political treatises, newspapers, accounting ledgers, naval records, and burial rituals (many from non-Anglophone sources)"--